(untitled) (Hungarian Journal of Industry and Chemistry, 2010)
Boring is presented in the article as well as drilling, errors in the drilling shape and position, and their control. The position of the holes is determined. It is possible to give the position of the holes in many ways. We are analysing the measurement results with a statistical method in the article. For example, we use distribution analysis, that is we apply a standard χ2 test to check if it is possible to define the measured variables according to a normal distribution. Finally, histograms and χ2 tests enable us to make a conclusion considering the errors, and we also propose the correction.